Measuring the Success Level and Effectiveness of Knowledge Management in Organizations: A Case Study - Mesbah, A.; Babaei, M.; Shabanali, A. (Engineering, Technology & Applied Science Research, 2017)
Knowledge management is a systematic approach to improve organizational ability to mobilize knowledge and facilitate decision-making in setting business strategy. This study identifies the outcomes of an effectively implemented knowledge management in one of the departments of ‘Iran Khodro’ as an empirical case study. Effective factors on effectiveness of knowledge management and effective outcomes of knowledge management were extracted by a semi-structured interview in three questions with 20 experts. Then, results of interviews and the factors extracted from literature were integrated; by removing similar factors, 52 factors were identified and organized in three groups. Using exploratory Delphi analysis in two stages (by expert’s judgments), 30 out of 52 factors extracted from literature and interview were identified as outcomes of knowledge management implemented in the organizations; these factors were evaluated through a second questionnaire in 32 questions for prioritization of their significance in the studied organization by experts and managers. Based on the coefficient calculated for the confirmed factors in three groups of outcomes, the top priority was knowledge, followed by human resource- organization and performance, respectively. Ranking of the rest is explained below.